2017
DOI: 10.1002/dc.23792
|View full text |Cite
|
Sign up to set email alerts
|

Oral pemphigus vulgaris: Liquid‐based cytological findings and pitfalls

Abstract: Pemphigus vulgaris (PV) is a chronic autoimmune bullous disease characterized by the formation of suprabasal cleavage and acantholysis. As this disease almost always affects the oral mucosa, conventional cytological smears of oral lesions can be used for the initial diagnosis of PV. We report two cases of PV that were initially diagnosed based on cytological smears of an oral sample. As atypical squamous cells were present even in the liquid‐based cytological (LBC) smears of the oral lesion in these two cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Another advantage of LBC smears is that they have a cleaner background than conventional smears. On the other hand, however, it has been reported that the LBC method does not confirm the strong perinuclear acid affinity staining characteristic of Tzanck cells 3,5 . We discovered that small, round‐shaped, and deeply stained atypical, orangeophilic, keratinized cells can be found not only in SCC but also in pemphigus (Figure 2A,C and Table 1).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Another advantage of LBC smears is that they have a cleaner background than conventional smears. On the other hand, however, it has been reported that the LBC method does not confirm the strong perinuclear acid affinity staining characteristic of Tzanck cells 3,5 . We discovered that small, round‐shaped, and deeply stained atypical, orangeophilic, keratinized cells can be found not only in SCC but also in pemphigus (Figure 2A,C and Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, however, it has been reported that the LBC method does not confirm the strong perinuclear acid affinity staining characteristic of Tzanck cells. 3,5 We discovered that small, round-shaped, and deeply stained atypical, orangeophilic, keratinized cells can be found not only in SCC but also in pemphigus (Figure 2A,C and Table 1). Although in Hara's paper, these cell characteristics are shown as one of the five practical items specific to oral squamous cell carcinoma, caution is required in the diagnosis of PV, since it has been reported that the diagnosis is difficult to make when small, round-shaped, and deeply stained atypical, orangeophilic keratinized cells are found in comparison of LBC cytology of cells from PV and SCC.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this case report, successfully periodontal treatment of a PV patient was presented. Certain diagnosis of the PV was based on the histopathological and immunofluorescence evaluation in accordance with the literature (1,7).…”
Section: Discussionmentioning
confidence: 89%